Sistem Rekapitulasi Absensi Karyawan Berbasis Web Pada Global English Language Center - Yudiastuti, Helda; Ibrahim, Irwansyah; Komalasari, Dinny; Miftahul Jannah, Wardah (Jurnal Ilmiah Matrik, 2024)
Abstract : Attendance is a routine on a working day carried out by an employee of an agency or company to prove that he is present or not. Attendance plays a very important role as an attendance list that will be used as the basis for calculating employee wages in the Company. Global English Language Center (GELC) is an institution where English courses are held, where employee attendance activities are currently still carried out manually, such as making attendance summaries with signed paper. There are several problems faced by GELC such as the accumulation of attendance documents, as well as the large number of photo files on the WhatsApp Group admin, making it difficult for admin staff to recap attendance. The purpose of this study is to create a website-based employee attendance recapitulation system. With this system, it is hoped that it will help the Staff and Admin of the Global English Language Center. The method that will be used in this study uses the waterfall method as a software development method.